Hearing pathways in the Yangtze finless porpoise, Neophocaena asiaeorientalis asiaeorientalis - Mooney, A.; Li, S.; Ketten, Darlene; Wang, K.; Wang, D. (The Company of Biologists Ltd, 2014)
How an animal receives sound may influence its use of sound. While ‘jaw hearing’ is well supported for odontocetes, work examining how sound is received across the head has been limited to a few representative species. The substantial variation in jaw and head morphology among odontocetes suggests variation in sound reception. Here, we address how a divergent subspecies, the Yangtze finless porpoise (Neophocaena asiaeorientalis asiaeorientalis) hears low-, mid- and high-frequency tones, as well as broadband clicks, comparing sounds presented at different locations across the head. Hearing was measured using auditory evoked potentials (AEPs). Click and tone stimuli (8, 54 and 120 kHz) were presented at nine locations on the head and body using a suction-cup transducer. Threshold differences were compared between frequencies and locations, and referenced to the underlying anatomy using computed tomography (CT) imaging of deceased animals of the same subspecies. The best hearing locations with minimum thresholds were found adjacent to a mandibular fat pad and overlaying the auditory bulla. Mean thresholds were not substantially different at locations from the rostrum tip to the ear (11.6 dB). This contrasts with tests with bottlenose dolphins and beluga whales, in which 30–40 dB threshold differences were found across the animals' heads. Response latencies increased with decreasing response amplitudes, which suggests that latency and sensitivity are interrelated when considering sound reception across the odontocete head. The results suggest that there are differences among odontocetes in the anatomy related to receiving sound, and porpoises may have relatively less acoustic ‘shadowing’.